Pengaruh Good Corporate Governance dan Profitabilitas Terhadap Nilai Perusahaan - Tanuwijaya, Patricia; Trisnawati, Luh Putu Puji (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
Firm value is one of the important indicators used by investors to assess a company's performance and future prospects. Efforts to increase firm value can be achieved through the effective implementation of Good Corporate Governance (GCG) and optimal profitability management. This study aims to analyze the effect of Good Corporate Governance, proxied by the board of directors, audit committee, and institutional ownership, as well as profitability, on firm value in infrastructure sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This study employed a quantitative approach using secondary data obtained from companies’ annual reports and financial statements. The sample was selected using a purposive sampling method based on predetermined criteria, resulting in 90 observations. Data were analyzed using panel data regression with the assistance of EViews 13 software. The results indicate that the board of directors and audit committee have no significant effect on firm value. Meanwhile, institutional ownership and profitability have a positive effect on firm value. These findings suggest that the role of institutional investors in monitoring management, as well as a company’s ability to generate profits, can enhance investor confidence and increase firm value. This study implies that companies should strengthen monitoring mechanisms through institutional ownership and improve profitability performance to enhance firm value from investors’ perspectives. The findings are expected to serve as a reference for corporate management and investors in making economic decisions.